Antidiabetic and Antihyperuricemic Activities of Salak Madu (Salacca edulis Reinw) Peel Extract in Alloxan- and High-Purine Diet-Induced Mice - Dzulrifaad Ubaidillah Al Afza; Neli Syahida Ni'ma (Journal of Science and Technology Research for Pharmacy, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by impaired carbohydrate, lipid, and protein metabolism. Hyperuricemia is a condition in which serum uric‑acid levels exceed normal values, namely > 7.0 mg/dL in men and > 6.0 mg/dL in women. Both antidiabetic and antihyperuricemic therapies can be administered pharmacologically and non‑pharmacologically; however, synthetic drugs often produce undesirable side effects. Concerns regarding these adverse effects have led many people to favour herbal remedies that are perceived as safer, one of which is the Salak Madu fruit. Salak Madu (Salacca edulis Reinw.), an emerging premium variety cultivated in Sleman, Yogyakarta, is rich in flavonoids with potential antihyperglycaemic and antihyperuricaemic properties. The present study evaluated the antidiabetic and antihyperuricemic activities of Salak Madu peel extract in vivo using alloxan‑induced and high‑purine‑diet mouse models. Mice were observed over 14 days and treated orally with peel extract at doses of 100, 200, and 400 mg/kg body weight (BW). On day 14, the 100 and 200 mg/kg BW doses produced significant reductions in blood‑glucose levels (P < 0.05), indicating a marked antihyperglycaemic effect in hyperglycaemic mice. For serum uric‑acid reduction, significant effects were observed on day 7 at doses of 200 and 400 mg/kg BW (P < 0.05), demonstrating a pronounced antihyperuricemic action in hyperuricemic mice.